Identification of Microplastics in Water and Fish in the Brantas River, Malang City - Parikesit, Anindya Rahmawati Putri; Harahab, Nuddin; Maharani Pertiwi K. (Jurnal Pembangunan dan Alam Lestari, 2026)
Microplastics constitute a significant source of pollution in the Brantas River waters. Classified as particles <5 mm in size, they originate from the decomposition of larger plastics. The growing population along the Brantas River Watershed is believed to contribute to the increase in microplastic pollution in the river. Therefore, this research was conducted to identify the types and presence of microplastics in water and fish samples collected from the waters of the Brantas River in Malang City. Sampling was carried out in September 2023 during the dry season. Water samples were collected at four research points, while fish samples were obtained from four points within the Brantas River Watershed, Malang City. The analysis process included sample filtering, drying and observation. Microplastic particles were documented and examined using a stereo microscope and their composition was determined using Fourier Transform Infra-Red (FTIR) tool to identify the polymer type. The prevalent microplastic type in the samples was film, predominantly black, and the most frequently identified polymers were nylon and nitrile. The highest abundance of microplastics was observed in water sample 3 and tombro fish (cyprinus carpio), with detailed amounts of 1.11 particles/m3 and 4.68 particles/m3 respectively. Keywords: Brantas Water, Cyprinus carpio, Microplastics, Oreochomis niloticus, Polymer.